2-Aminobenzoic acid-4-(pyridin-4-yldisulfanyl)pyridine (1/1) - Arman, H.D.; Kaulgud, T.; Tiekink, E.R.T. (International Union of Crystallography, 2011)
The title 1:1 co-crystal, C(7)H(7)NO(2)center dot C(10)H(8)N(2)S(2), features a highly twisted 4-(pyridin-4-yldisulfanyl) pyridine molecule [dihedral angle between the pyridine rings = 89.06 (10)degrees]. A small twist is evident in the 2-aminobenzoic acid molecule, with the C-C-C-O torsion angle being -7.7 (3)degrees. An N-H center dot center dot center dot O hydrogen bond occurs in the 2-aminobenzoic acid molecule. In the crystal, molecules are linked by O-H center dot center dot center dot N and N-H center dot center dot center dot N hydrogen bonds into a supramolecular chain along the b axis. These are connected into layers by pi-pi interactions occurring between pyridine rings [centroid-centroid distance = 3.8489 (15)angstrom]. The layers are connected along the a axis by C-H center dot center dot center dot O contacts. The crystal studied was a racemic twin.